Effect of seedlings age, cultivars and weed management on weed dynamics, nutrient removal and yield of rice (Oryza sativa) under system of rice intensification (SRI) - SHUKLA, U N; SRIVASTAVA, V K; SINGH, SMITA; RAM, U S; PANDEY, A K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted to study the effect of age of seedlings, cultivars and weed management on weed dynamics, NPK removal and yield of rice (Oryza sativa L.) under SRI at Banaras Hindu University, Varanasi during 2010 and 2011 in split-plot design replicated thrice. The tender aged seedling (10 days) and hybrid rice cultivar PHB 71 had significantly marked potential to minimize the weed dynamics of grassy weeds (Echinochloa spp. and Cynodon dactylon), sedges (Fimbristylis miliacea and Cyperus spp.) and BLWs (Ammania baccifera and Ludwigia parviflora) significantly that resulted in marked reduction on total weed density, weed dry weight, weed index resulted in higher weed control efficiency over older seedling (15 days) of NDR 359. Four times cono-weeding at 10, 20, 30 and 40 DAT minimised grassy weeds over rest of the weeding treatments, but at par with pre and post-emergence application of pretilachlor + bispyribac-Na herbicides in respect of sedges and BLWs with total weed density that resulted in improving weed index due to higher weed control efficiency over 15 days old seedlings and other weed management treatment during both the years of study. Similarly, transplanting of younger seedlings (10 days) of PHB 71 produced significantly higher rice yield under 4 times cono-weeding closely followed by pre and post-emergence application of pretilachlor + bispyribac-Na. Significantly lower NPK removal by weeds at 45 DAT recorded with 10 days old seedling of PHB-71 under 4 times cono-weeding at 10, 20, 30 and 40 DAT (W4), though remained at par with pre and post-emergence application of pretilachlor + bispyribac-Na.